Kewenangan KPU Dalam Menetapkan Regulasi Pemilu Studi Pemutakhiran Data dan Penyusunan Daftar Pemilih Pemilu Serentak 2024 - Rusdi; Ricky Febriansyah (Fakultas Hukum Universitas Islam Indonesia, 2023)
Abstract This article discusses the authority of the General Election Commission (KPU) in establishing General Election Commission (PKPU) Regulations. By taking a study of the stages of updating voter data in the 2024 simultaneous elections. The research method of this article uses a normative-empirical method with a conceptual approach, a statutory approach, and a case approach. The results of this study show 1). KPU is given the authority to issue PKPU Number 7 of 2023 concerning Amendments to PKPU Number 7 of 2022 concerning Compilation of voter lists in holding general elections and voter data information systems; 2). KPU stipulates technical guideline regulations and several circular letters to be guided by Provincial/District/City KPU, 3). De jure implementation in updating voter data needs to be matched with the Ministry of Home Affairs regulations regarding population data. The conclusion in this article is that the KPU needs to collaborate with the Ministry of Home Affairs from the central to the regional levels in updating voter data on a de jure basis.